HIGH SENSITIVE C-REACTIVE PROTEIN AND ITS RELATIONSHIP WITH OTHER CARDIOVASCULAR RISK VARIABLES IN OBESE, OVERWEIGHT AND HEALTHY INDIVIDUALS - B, Gayathri; Vm, Vinodhini (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: More than 50% of the world's population is considered overweight and being overweight is associated with several comorbidities such as Type 2 diabetes mellitus, hypertension, cardiovascular diseases, dyslipidemia, respiratory diseases, osteoarthritis, and depression. Therefore, in this study, we have estimated the high sensitive C-reactive protein (hs-CRP) levels in obese, overweight, and normal body mass index (BMI) individuals and whether there was any relationship between hs-CRP and other risk factors of the cardiovascular system such as serum total cholesterol (TC) and other lipids. Methods: A total of 150 participants, divided into three groups. Group I - 50 participants with normal BMI (18–22.99 kg/m2), Group II - 50 participants who were overweight (BMI = 23–24.99 kg/m2), and Group III - 50 who were obese (BMI ≥25 kg). We measured fasting plasma glucose, postprandial plasma glucose, serum TC, triacylglycerol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, and hs-CRP. Results: Obese individuals had increased hs-CRP compared with control (Group I) and overweight (Group II) groups. hs-CRP positively correlated with BMI and lipid profile. Conclusion: Elevated hs-CRP was associated with cardiovascular risk factors in overweight and obese individuals. This high-risk group should be targeted for therapeutic lifestyle modifications to prevent further complications.